Interleukin-7 receptor blockade suppresses adaptive and innate inflammatory responses in experimental colitis - Willis Cynthia R; Seamons Audrey; Maxwell Joe; Treuting Piper M; Nelson Laurel; Chen Guang; Phelps Susan; Smith Carole L; Brabb Thea; Iritani Brian M; Maggio-Price Lillian (BMC, 2012)
Abstract Background Interleukin-7 (IL-7) acts primarily on T cells to promote their differentiation, survival, and homeostasis. Under disease conditions, IL-7 mediates inflammation through several mechanisms and cell types. In humans, IL-7 and its receptor (IL-7R) are increased in diseases characterized by inflammation such as atherosclerosis, rheumatoid arthritis, psoriasis, multiple sclerosis, and inflammatory bowel disease. In mice, overexpression of IL-7 results in chronic colitis, and T-cell adoptive transfer studies suggest that memory T cells expressing high amounts of IL-7R drive colitis and are maintained and expanded with IL-7. The studies presented here were undertaken to better understand the contribution of IL-7R in inflammatory bowel disease in which colitis was induced with a bacterial trigger rather than with adoptive transfer. Methods We examined the contribution of IL-7R on inflammation and disease development in two models of experimental colitis: Helicobacter bilis (Hb)-induced colitis in immune-sufficient Mdr1a−/− mice and in T- and B-cell-deficient Rag2−/− mice. We used pharmacological blockade of IL-7R to understand the mechanisms involved in IL-7R-mediated inflammatory bowel disease by analyzing immune cell profiles, circulating and colon proteins, and colon gene expression. Results Treatment of mice with an anti-IL-7R antibody was effective in reducing colitis in Hb-infected Mdr1a−/− mice by reducing T-cell numbers as well as T-cell function. Down regulation of the innate immune response was also detected in Hb-infected Mdr1a−/− mice treated with an anti-IL-7R antibody. In Rag2−/− mice where colitis was triggered by Hb-infection, treatment with an anti-IL-7R antibody controlled innate inflammatory responses by reducing macrophage and dendritic cell numbers and their activity. Conclusions Results from our studies showed that inhibition of IL-7R successfully ameliorated inflammation and disease development in Hb-infected mice by controlling the expansion of multiple leukocyte populations, as well as the activity of these immune cells. Our findings demonstrate an important function of IL-7R-driven immunity in experimental colitis and indicate that the therapeutic efficacy of IL-7R blockade involves affecting both adaptive and innate immunity.